THE IMPACT OF SPONSORSHIP, EVENT, AND PUBLICITY TO CONSUMER DECISION MAKING OF PT. HASJRAT ABADI - Poluakan, Indah Heidy; Pangemanan, Sifrid S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Promotion is one of tools that support marketing part to introduce the products to customers. Various promotional techniques are used by the marketer to influence the consumer decision making. Promotional mix such as Advertising, Sales Promotion, Publicity/Public Relations, Personal Selling are generally used. This research is conduct in Manado. The objectives of this research are to analyze the impact of sponsorship, event, and publicity to consumer decision making, partially and simultaneously. This research is causal type of research where it will investigate the impact sponsorship, event, and publicity to consumer decision making. Using a multiple regression model to answer the research problem. The population in this study is a costumers of PT.Hasjrat Abadi in Manado, whereas samples taken by each respondents 100 respondents. The hypothesis testing , this research conduct a conclusion of there is significant effect of sponsorship and publicity partially to consumer decision making, and there is significant effect of sponsorship, event, and publicity simultaneously to consumer decision making, whereas event does not have significant effect partially to consumer decision making. This study reveals that sponsoring activities and publish the product has a strong effect to the consumer in order to investigate, select, and buy a product, they prefer to purchase a product with a well know branded. Keywords: promotional mix, sponsorship, publicity.